ANALISIS KRIMINALISASI PENGGUNA JASA PROSTITUSI DALAM MEMINIMALISIR PRAKTEK PROSTITUSI - Mariyam, Siti; Satria, Adhi Putra (Universitas Muhammadiyah Ponorogo, 2024)
This article aims to examine and analyze the phenomenon of prostitution services and evaluate the effectiveness of criminalizing users of prostitution services in reducing current prostitution practices. The article is written using a legal, empirical, and comparative approach, with data based on secondary sources. The analysis results indicate that prostitution can be fundamentally interpreted as the commercialization of sexual relationships, where an individual provides sexual services to another in exchange for money. In the present era, many studies emphasize the significant meaning of criminalizing users of prostitution services, as exemplified by the measures taken in Sweden. However, despite Sweden's attempt to criminalize by imposing fines on users of prostitution services, the practice of prostitution persists. Criminalization can lead to new issues, such as the emergence of human trafficking practices and an increase in the spread of HIV due to inadequate supervision of covert prostitution practices.